Wireless and wired remote measrement unit design and applications - Khan, Sheroz; Islam, Md. Rafiqul; Khalifa, Othman Omran (2004)
Remote data acquisition is of critical importance in applications such as machine health monitoring in heavy industries and energy consumption in the cases of electricity consumer population spreading over a wide geographical area. Remote measuring units with wireless means for transmission have extended the scope of measurements in cases that are difficult to access or difficult for wired data acquisition. Once the data is available for being archived in control centers, then wired medium is used for its transmission to component departments within the same premises using RS-485 as a medium of transmission. This paper presents the design of a prototype data acquisition board, which is cable to transmit data to a remote computer through asynchronous wireless means. Also, this work is suggesting how data is transmitted to nearby departments using RS-232 as a medium of transmission within the same premises. This RMU has got numerous industrial and commercial applications including data acquisition, monitoring and control in situations which are otherwise difficult to access. One application for this proposed remote measurement unit is to transmit units of electrical energy to a nearby utility center. The second application is that of transmission of data using RS-232 as a medium within the same premises. The design of a data acquisition board embodies features to acquire data from a number of analogue and digital sources, and to store that data on board before being sent out using wireless means. The data stored on board is displayed on an LCD and a computer at the sending end, which is then sent to a remote receiving end board station via ATM. At the receiving board station the data is on LCD before being archived on a computer which is physically far apart from a monitoring station, thus pushing the need for major developments in instrumentations. This prototype is developed as a work of undergraduate and postgraduate projects carried out under the authors' supervision.